DASHBOARD INFORMATION SYSTEM OF PEMINJAMAN UANG (PINANG) APPLICATION - Andiani, Andiani; Zidni L, M Farhan (Kresnamedia Publisher, 2020)
Pinang is a digital application-based BRI Agro product that runs on the Android operating system, where with this application customers can apply for loans without collateral digitally, anywhere and anytime. In its journey, the Pinang application certainly does not run smoothly, the application should continue to grow and must be able to face challenges from various sectors, as well as the system that runs on the Pinang application, which has continued to be developed to date, in line with the increasing number of users of the Pinang application. This makes it difficult for the operational team to manage and monitor user data with the number of users increasing day by day if they continue to use conventional methods. Of course, we need a system that can help the process of managing data from Pinang customers, starting from adding company cooperation with the Pinang application to maintaining and monitoring the system digitally. So a Pinang dashboard information system was created that can assist in the operation of the Pinang application that is able to manage data, monitor and maintain if there are problems in the Pinang application borrowing process. The Pinang dashboard can make it easier to manage, monitor and provide information related to the Pinang application. The areca dashboard is built using the waterfall model. The result of this research is the creation of a dashboard information system for the Pinang money lending application.